Immigration and electoral outcomes: Evidence from the 2015 refugee inflow to Germany - Julia Bredtmann (RWI - Leibniz-Institut für Wirtschaftsforschung, 2020)
This paper investigates the effects of the 2015 mass inflow of refugees to Germany on electoral outcomes. Specifically, using unique data on refugee populations and their type of accommodation, I analyze how local exposure to refugees affects the outcomes of the March 2016 state election - an election that was characterized by a strong surge in the electoral success of right-wing parties. For identification, I exploit quasi-random variation in the allocation of refugees across municipalities. The results show that an increase in the population share of refugees increases the vote share of right-wing parties and decreases the vote share of the incumbent federal government parties. The electoral effects, however, are solely driven by refugees living in centralized accommodation, and particularly by municipalities that host reception centers for refugees. These findings have important implications for the design of public policies in handling future receptions of refugees, as they reveal that an earlier transfer of refugees from centralized to decentralized accommodation could attenuate a growing support for right-wing parties. – – Die vorliegende Studie untersucht den Einfluss des starken Zuzugs von Geflüchteten nach Deutschland im Jahr 2015 auf Wahlergebnisse. Auf Basis von Daten zur regionalen Verteilung von Geflüchteten sowie deren Art der Unterbringung wird konkret untersucht, inwiefern lokaler Kontakt zu Geflüchteten die Ergebnisse der Landtagswahl im März 2016 beeinflusste - eine Wahl, die durch einen enormen Anstieg des Erfolgs rechter Parteien geprägt war. Die Ergebnisse zeigen, dass ein höherer Anteil an Geflüchteten in der Bevölkerung den Stimmanteil von rechten Parteien erhöht und den Stimmanteil der amtierenden Regierungsparteien im Bundestag verringert. Diese Wahleffekte sind jedoch ausschließlich auf Geflüchtete zurückzuführen, die in zentralen Einrichtungen leben, und insbesondere auf solche Gemeinden, die Erstaufnahmeeinrichtungen für Geflüchtete betreiben. Diese Ergebnisse zeigen, dass ein schnellerer Übergang von Geflüchteten von einer zentralen in eine private Unterbringung eine zunehmende Unterstützung rechter Parteien in der Bevölkerung abmildern kann, und haben damit eine wichtige Bedeutung für die Ausgestaltung von Politikmaßnamen im Zusammenhang mit der Handhabung zukünftiger Flüchtlingszuzüge.
Keywords: D72; F22; J15; R23; 330; Immigration; refugees; political economy; voting